Pipeline Diameter Significantly Impacts the Long-Term Fate of Jailed Side Branches during Treatment of Intracranial Aneurysms - Miller, T.R.; Kole, M.J.; Le, E.J.; Cannarsa, G.; Jones, S.; Wessell, A.P.; Jindal, G.; Aldrich, E.F.; Simard, J.M.; Gandhi, D. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Although covered side branches typically remain patent acutely following Pipeline Embolization Device embolization of intracranial aneurysms, the long-term fate of these vessels remains uncertain. We therefore elected to investigate factors that may influence the long-term patency of these covered side branches.MATERIALS AND METHODS: We retrospectively evaluated the long-term patency of side branches covered by the Pipeline Embolization Device at our institution during treatment of intracranial aneurysms with at least 6 months of conventional angiography follow-up. Procedural and anatomic factors that might influence the fate of covered side branches were explored.RESULTS: One hundred forty-eight Pipeline Embolization Device treatments in 137 patients met the inclusion criteria. In 217 covered side branches, 29 (13.4%) were occluded on follow-up, and 40 (18.4%) were stenotic. All stenoses and occlusions were asymptomatic. In the entire cohort and in the largest subset of ophthalmic arteries, a smaller Pipeline Embolization Device diameter was associated with branch vessel occlusion (P = .001, P = .013). When we considered stenotic and occluded side branches together, smaller Pipeline Embolization Device size (P = .029) and administration of intraprocedural abciximab (P = .03) predicted side branch stenosis/occlusion, while anterior choroidal branch type (P = .003) was a predictor of gross side branch patency.CONCLUSIONS: A smaller Pipeline Embolization Device diameter is associated with delayed side branch stenosis/occlusion following Pipeline Embolization Device treatment, likely due to the higher metal density of smaller caliber devices. Although hemodynamic factors, including the potential for collateral flow, are still paramount in determining the fate of covered side branches, the amount of metal coverage at the side branch orifice also plays an important role.PEDPipeline Embolization Device